Artemisia vulgaris L. ethanolic leaf extract reverses thrombocytopenia/ thrombocytosis and averts end-stage disease of experimental severe Plasmodium berghei murine malaria - Bamunuarachchi, Gayan S.; Ratnasooriya, Wanigasekara D.; Premakumara, Sirimal; Udagama, Preethi V. (J Vector Borne Disease, 2014)
Background & objectives: Artemisinin isolated from Artemisia annua is the most potent antimalarial against chloroquine resistant Plasmodium falciparum malaria. We previously reported that the ethanolic leaf extract of Artemisia vulgaris, an invasive weed and the only Artemisia species in Sri Lanka, possess both potent and safe antimalarial activity (in terms of antiparasitic properties) in a P. berghei murine malaria model. We report here a prototype study that investigated antidisease activities of A. vulgaris ethanolic leaf extract (AVELE) in a P. berghei ANKA murine malaria model that elicit pathogenesis similar to falciparum malaria. Profound thrombocytosis and thrombocytopenia in mice were detected in early-stage (Day 3), and at a later stage of infection (Day 6), respectively. Plasmodium berghei infected mice, 7 or 8 days post-infection reached end-stage disease with rapid drop in body temperature and usually die within 24 h, as a consequence of cerebral malaria. Methods: Three doses of the AVELE (500, 750 and 1000 mg/kg) were used to assess antidisease activity of A. vulgaris in terms of survival, effects on thrombocyte related pathology and end-stage disease, antipyretic activity, and antinociception, using standard methodology. Results: The 1000 mg/kg dose of AVELE significantly increased survival, reversed the profound thrombocytopenia/ thrombocytosis (p ≤0.01), altered the end-stage disease (p ≤0.05), and manifested significant antipyretic and antinociceptive (p ≤0.05) activities. Interpretation & conclusion: We conclude that a crude ethanolic leaf extract of A. vulgaris, showed potent antimalarial properties, in terms of antidisease activities; antipyretic activity, peripheral and central antinociception, increased survival, averted end-stage disease and reversed thrombocytopenia/thrombocytosis
Keywords: end-stage disease; thrombocytopenia/ thrombocytosis reversal; Antidisease activity; Artemisia vulgaris; Plasmodium berghei ANKA; Sri Lanka